2015
DOI: 10.5713/ajas.14.0480
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Holstein Dairy Cows Grazing in Dry-summer Subtropical Climatic Conditions: Effect of Heat Stress and Heat Shock on Meiotic Competence and In vitro Fertilization

Abstract: The present study was designed to evaluate how environmental factors in a dry-summer subtropical climate in Terceira-Azores (situated in the North Atlantic Ocean: 38° 43′ N 27° 12′ W) can affect dairy cow (Holstein) fertility, as well as seasonal influence on in vitro oocytes maturation and embryos development. Impact of heat shock (HS) effects on in vitro oocyte’s maturation and further embryo development after in vitro fertilization (IVF) was also evaluated. For such purpose the result of the first artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Global warming, nutritional variability and increase of metabolic disorders are factors affecting both human and animal reproduction (Sirotkin, 2010), environmental heat stress is one of the major factors affecting animals, particularly lactating cows (Dunlap & Vincent, 1971; Badinga et al , 1985; Pavani et al , 2015b). Summer heat factors, such as high temperature humidity indexes (THI), are major problems for the dairy industry and contribute to economic losses among about 60% of the world's cattle population (Edwards et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global warming, nutritional variability and increase of metabolic disorders are factors affecting both human and animal reproduction (Sirotkin, 2010), environmental heat stress is one of the major factors affecting animals, particularly lactating cows (Dunlap & Vincent, 1971; Badinga et al , 1985; Pavani et al , 2015b). Summer heat factors, such as high temperature humidity indexes (THI), are major problems for the dairy industry and contribute to economic losses among about 60% of the world's cattle population (Edwards et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that an increase in THI (≥72) affects the body temperature of dairy cows (Armstrong, 1994), which leads to hypothermia and impairs the cellular function of various tissues and parts of the reproductive system (Wolfenson et al , 2000). Heat-induced hypothermia studies, both in vivo and in vitro , have shown that rectal temperature may reach or exceed 41°C (Ealy et al , 1993), which impairs hormonal secretion, oocyte fertilization and embryo development (Wolfenson et al , 2000; Rivera & Hansen, 2001; Sartori et al , 2002), resulting in a decrease in pregnancy rate of approximately 25% for every 1°C increase in rectal temperature (Pavani et al , 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments developed by our team show that exposing cumulus oocyte complexes (COCs) to 41°C did not alter the number of embryos that cleaved but reduced significantly the percentage of development in the blastocyst stage [9]. Additionally, the exposure of bovine embryos to heat shock during oocyte maturation leads to embryos with reduced development and induced alterations in protein synthesis and possibly gene expression as early as the two-cell embryos.…”
Section: The Hspa14 Genementioning
confidence: 99%
“…Before ovulation, there are several physiological factors that can disrupt establishment of pregnancy changes by elevated thermal heat. Heat shock effects endometrial prostaglandin secretion, oocytes during maturation period, and decreases low fertility of dairy cows in hot seasons [9]. Moreover, heat stress was suggested to be similar to oxidative stress, because of correspondences in the genes expressed after heat exposure, such as genes encoding heat shock proteins (HSPA14 gene), demonstrated heat-induced increase of reactive oxygen species (ROS) production, especially the superoxide anion.…”
Section: Studies Onmentioning
confidence: 99%
See 1 more Smart Citation